2019
DOI: 10.1364/oe.27.024018
|View full text |Cite
|
Sign up to set email alerts
|

Spatial beam self-cleaning and supercontinuum generation with Yb-doped multimode graded-index fiber taper based on accelerating self-imaging and dissipative landscape

Abstract: We experimentally demonstrate spatial beam self-cleaning and supercontinuum generation in a tapered Ytterbium-doped multimode optical fiber with parabolic core refractive index and doping profile when 1064 nm pulsed beams propagate from wider (120 µm) into smaller (40 µm) diameter. In the passive mode, increasing the input beam peak power above 20 kW leads to a bell-shaped output beam profile. In the active configuration, gain from the pump laser diode permits to combine beam self-cleaning with supercontinuum … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…Previously, we experimentally demonstrated Kerr-beam self-cleaning (KBSC) in a 10 m long tapered, YD graded-index (GRIN) MMF when pulses were launched from the wider (120 µm) into the smaller (40 µm) core [6]. We observed self-cleaning without significant frequency conversion in the passive regime (without the pump laser diode).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Previously, we experimentally demonstrated Kerr-beam self-cleaning (KBSC) in a 10 m long tapered, YD graded-index (GRIN) MMF when pulses were launched from the wider (120 µm) into the smaller (40 µm) core [6]. We observed self-cleaning without significant frequency conversion in the passive regime (without the pump laser diode).…”
mentioning
confidence: 87%
“…We observed self-cleaning without significant frequency conversion in the passive regime (without the pump laser diode). On the other hand, the presence of gain from the pump led to a beam cleanup which was accompanied by ultrawideband frequency conversion and supercontinuum generation, extending from 520 nm to 2600 nm [6]. It should be noted that frequency conversions should be avoided in high power fiber lasers.…”
mentioning
confidence: 99%
“…In order to further expand the possibilities of controlling the spatial and spectral shaping of multimode beams, we developed an Yb-doped MMF taper, with parabolic index and doping profiles in the core, whose diameter is exponentially decreasing along the 10 m long taper from 120 µm to 40µm. Tapering leads to an acceleration of the self-imaging oscillations in the MMF: Niang et al directly measured the self-imaging period along the MMF taper, and obtained that it decreases from 1.2 mm at the large core diameter end, down to 360 µm at the small diameter side [11].…”
Section: Dissipative Landscapementioning
confidence: 99%
“…As can be seen, the output beam diameter fluctuates wildly at low powers, while for peak powers above 20 kW it stabilizes to about 20.5 µm. In the presence of gain induced by a laser diode pump, the accelerating self-imaging leads to a continuous up-shift of the anti-Stokes geometric parametric instability (GPI) sidebands along the taper [11], which permits to broaden into the visible region the supercontinuum (SC) generated at the taper output (see Fig. 4), extending between 520 and 2600 nm.…”
Section: Dissipative Landscapementioning
confidence: 99%
“…In recent experiments, Niang et al demonstrated spatial beam self-cleaning and supercontinuum generation (between 520 and 2600 nm) in a tapered Ytterbium-doped MMF with parabolic core refractive index and doping profiles [30]. By taper cut-back, longitudinal switching of different self-cleaned modes was also observed.…”
Section: Spatial Beam Shapingmentioning
confidence: 99%